Hydrodynamic behavior and dilute solution properties of Ulva fasciata algae polysaccharide - Shao, P.; Zhu, Y.; Qin, M.; Fang, Zhongxiang; Sun, P. (Elsevier Ltd, 2015)
Hydrodynamic behavior and dilute solution properties of Ulva fasciata polysaccharides (UFP) were investigated. Experimental results indicated that the variation of hydrodynamic behavior of UFP was affected by the type and concentration of salts. The specific viscosity of UFP in water increased with its increasing concentration. The slopes of the double logarithmic plots in the dilute and semi-dilute solutions were 0.86 and 1.99, respectively. The molecular conformation could be semi-flexible like. Huggins plots of UFP solutions in the presence of salts including Na+, K+, Mg2+ and Ca2+ showed that the hydrodynamic behavior of the UFP was strongly affected by the types and strength of salt ion. The stiffness parameter of UFP solution was 0.1149, higher than that of other reported polysaccharides, indicating that it could tolerate high salt concentration. Dynamic rheological results suggested that 0.5% UFP solution was a typical characteristic of polymer solution in the dilute region. This work provided some valuable and fundamental information in understanding the physicochemical properties of UFP solution.